2017
DOI: 10.1016/j.jjcc.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Andersen-Tawil syndrome: Clinical presentation and predictors of symptomatic arrhythmias – Possible role of polymorphisms K897T in KCNH2 and H558R in SCN5A gene

Abstract: Background Andersen-Tawil syndrome (ATS) is rare channelopathy caused by KCNJ2 mutation and probably KCNJ5. It is characterized by arrhythmias, neurological symptoms, and dysmorphic features. The present study retrospectively examined the characteristics of 11 unrelated families with ATS. Methods This study consisted of 11 probands positive for KCNJ2 variants and 33 family members (mean age 30.0 ± 17.3 years, female n=31). Additional genetic screening of 3 LQTS genes (KCNQ1, KCNH2, SCN5A) was performed in 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Our finding concord with the study by Yoon et al (2006), who observed mandibular hypoplasia in all 10 examined subjects through anthropometric evaluation. Differently, in studies on KCNJ2 mutation carriers by Tristani‐Firouzi et al (2002) and Krych et al (2017), a small mandible was observed in 16/36 (44%) and 15/25 (60%) patients respectively. Phenotypic variability in ATS is well known and may explain that discrepancy; nevertheless, a quantitative evaluation of facial structures can detect small variations which might not be noticed on a mere visual inspection of patients.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our finding concord with the study by Yoon et al (2006), who observed mandibular hypoplasia in all 10 examined subjects through anthropometric evaluation. Differently, in studies on KCNJ2 mutation carriers by Tristani‐Firouzi et al (2002) and Krych et al (2017), a small mandible was observed in 16/36 (44%) and 15/25 (60%) patients respectively. Phenotypic variability in ATS is well known and may explain that discrepancy; nevertheless, a quantitative evaluation of facial structures can detect small variations which might not be noticed on a mere visual inspection of patients.…”
Section: Discussionmentioning
confidence: 84%
“…We analyzed facial features pooling male and female data, after verifying they were not different. Krych et al (2017) reported that few studies analyzed data concerning ATS manifestations in both sexes, with contrasting results in relation to cardiac and skeletal muscle phenotypes; Andelfinger et al (2002) did not find sex specificity for dysmorphic features.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of these devices in cardiac rehabilitation is undisputed [ 33 ]. Currently, we are starting a long-term observation study of patients with Long QT syndrome type VII, employing modern HRMs for use in ultramarathoners (long “battery life”) [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a long-term observational study of patients with long QT syndrome type VII is performed, employing modern HRMs (with long "battery life") for use in ultramarathoners [30,31].…”
Section: Strap Hrms or Optical Hrm?mentioning
confidence: 99%